STUDENTS ATTITUDE TOWARDS THE OMISSION OF NATIONAL EXAMINATION IN VOCATIONAL HIGH SCHOOL OF TELADAN PEMATANG SIANTAR - Kristiani Siagian; Tiarma Intan Marpaung; Mungkap Mangapul Siahaan (JURNAL ILMIAH RESEARCH STUDENT, 2023)
This research was carried out to determine whether or not there were negative or positive characteristics of students regarding the omission of the national exam at Vocational High School of Teladan Pematang Siantar. The research methodology used in this research is a descriptive qualitative method. There was only 1 class used as a sample for this research, namely class XI RPL 2. Data collection was carried out using a questionnaire. Research findings show that there are positive characteristics of using questionnaires towards the omission of national exams. It can be seen that the result is 85, where this result is on a positive scale. This is based on a questionnaire in the RPL 2 class which shows that students' opinions are positive regarding the omission of national examination.